Roy, Alexis. 2025. « Richard Sandbrook Et Robin Cohen (dir.) (2023) - The Development of an African Working Class ». Revue d’histoire Contemporaine De l’Afrique, nᵒ 6-7 (février):1-2 - (:unkn) unknown (My University, 2024)
Roy, Alexis. 2025. « Richard Sandbrook Et Robin Cohen (dir.) (2023) - The Development of an African Working Class ». Revue d’histoire Contemporaine De l’Afrique, nᵒ 6-7 (février):1-2
Keywords: African Research